ChemInform Abstract: Palladium‐Catalyzed Regio‐ and Stereoselective Cross‐Addition of Terminal Alkynes to Ynol Ethers and Synthesis of 1, 4‐Enyn‐3‐ones. Issue 30 (July 2015) - Hari Babu, Madala; Dwivedi, Vikas; Kant, Ruchir; Sridhar Reddy, Maddi
Abstract The title reaction proceeds in a highly regio‐ and stereoselective manner.